Four new Zn(ii) and Cd(ii) coordination polymers using two amide-like aromatic multi-carboxylate ligands: synthesis, structures and lithium–selenium batteries application. Issue 26 (14th May 2019) - Cheng, Qiuxia; Qin, Luzhu; Ke, Chunxian; Zhou, Jianen; Lin, Jia; Lin, Xiaoming; Zhang, Gang; Cai, Yuepeng
Abstract : Four new coordination polymers were constructed and compound2 was used as a host to active selenium for Li–Se batteries. Abstract : Four new coordination polymers, {[Zn(3-PBI)(H2 O)]·2DMF} n (1 ), [Cd(3-PBI)(DMF)] n (2 ), {[Zn4 (μ4 -O)(4-PBI)3 ]·3DMF} n (3 ), {[Cd4 (4-PBI)4 (H2 O)6 ]·13H2 O} n (4 ), have been constructed from two isomeric flexible multi-carboxylate ligands, 3-H2 PBI = 5-(3-(pyridin-3-yl)benzamido)isophthalic acid and 4-H2 PBI = 5-(3-(pyridin-4-yl)benzamido)isophthalic acid. Structural analysis reveals that compound1 is a one-dimensional (1D) ladder-like chain assembled by Zn(ii ) ions and 3-PBI 2− ligands, which further extend into a 3D supramolecular structure through π⋯π stacking and interlayer (O–H⋯O) hydrogen bonding interactions. In compound2, Cd 2+ metal ions are connected by carboxylate groups to form [Cd2 (COO)4 ] secondary building units (SBUs). The whole framework possesses a quadrilateral channel and constitutes a unique 3D (3, 6)-connected rutile net with the Schläfli symbol of (4 2 ·6 10 ·8 3 )(4·6 2 )2 . As for3, Zn(ii ) ions are bridged by one μ4 -O and six carboxylate groups to form a tetranuclear [Zn4 (μ4 -O)(COO)6 ] cluster, resulting in a rare (3, 9)-connected 3D network. Compound4 has an appealing 2D layered architecture involving two distinct topologies in the crystal structure, stacking in an unusual ABBABB mode (where A represents (4·8 2 ) topology and B denoteskgd topology). Moreover, compound2 is prepared as a support for active selenium through a melt-diffusion method. The obtained Cd-CP/Se electrode can be tested for lithium–selenium batteries and shows an initial capacity of 514 mA h g −1 and a reversible capacity of 200 mA h g −1 at 1C after 500 cycles. The good storage performance of Cd-CP/Se demonstrates it to be a prospective cathode material for lithium–selenium batteries.